Teaching Rheumatology to Medical Students: Current Practice and Future Aims - Jones, Adrian (J R Coll Physicians Lond, 1992)
Rheumatological disease is common but is often overlooked or inadequately assessed by doctors. This may reflect training in the discipline. The results of a survey of all British medical schools by the Arthritis and Rheumatism Council and the British Society for Rheumatology show that clinical rheumatology teaching forms a small part of most courses (median 4, range 0—8 weeks), usually as a second-year specialty attachment, and that specific assessment of basic clinical skills in rheumatology is often not undertaken. The results of the survey support the idea that the current teaching of rheumatology might help to marginalise the subject rather than to promote it.